Nanotubes: Self‐Compensated Insulating ZnO‐Based Piezoelectric Nanogenerators (Adv. Funct. Mater. 44/2014). (November 2014) - Kim, Dohwan; Lee, Keun Young; Gupta, Manoj Kumar; Majumder, Subrata; Kim, Sang‐Woo
<x xml:space="preserve">Abstract</x> High performance piezoelectric nanogenerators based on self‐compensated insulating ZnO via native defect control are demonstrated by S.‐W. Kim and co‐workers on page 6949. Self‐compensation of donor and acceptor type native defects makes ZnO insulating. Without additional passivation agents, dramatic enhancement of the piezoelectric output performance is observed compared to a donor defect rich ZnO NG under same mechanical strain. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>